Cardiac rehabilitation interventions in caregivers of a patient with cardiac disease: scoping review protocol - Loureiro, Maria (2020)
Cardiac Rehabilitation (CR) is a multi-component intervention generally composing of structured exercise training, psychological support and education to promote positive lifestyle changes in patient with different heart disease. However, it´s not possible to forget the role of patient´s caregivers in their health. They contribute substantially to patient’s management of and recovery from cardiovascular disease. In this context of cardiac disease, caregivers provide support to people living with long-term conditions, so it’s essential to know the evidence of interventions that support caregivers in their role. In addition to their role, it is clear that in some cardiac diseases, there is a genetic / hereditary component and that risk behaviors are often shared between cohabitants. So, it is also essential to understand whether a cardiac rehabilitation intervention is also necessary for the family / caregiver. Objetives: Examine and map which cardiac rehabilitation interventions have been implemented and evaluated that support caregivers of patient with cardiac disease in their role and health. Methods : Scoping reviews developed by the Joanna Briggs Institute. Results and Discussion: This scoping review will consider studies that focus on caregiver of patient with medical or surgery heart disease, assisted by cardiac rehabilitation teams. Conclusions Caregivers of patients with heart disease have the same right to be cared for as their sick family members, for a healthy transition, an adequate exercise in their caregiver role and maintenance/improvement of their health. It is, therefore essential to understand which interventions and contexts are suitable for cardiac rehabilitation programs targeted to caregivers.